Augusto: el principado y la organización del estado - Buisel, María Delia (Centro de Estudios Latinos. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2014)
We aim to study the principal stages of the August’s life and his political plot: a) from the Julius Caesar’s murder to Philippi, b) from Philippi to Actium, c) from Actium to 27 b.C., d) from 27 b.C. to 12 b.C., e) from Pontifex Maximus to his death. This means to characterize the Principate, the progressive assumption of the public power and to distinguish the meaning of potestas, imperium, maiestas, auctoritas, pax, notions with which Augustus achieves the organization of the Roman state with republican institutions, restored after civil war or created during the Principate